Bovine alphaherpesvirus type 5 replicates more efficiently than bovine alphaherpesvirus type 1 in undifferentiated human neural cells - Rosales, Juan Jose; Verna, Andrea Elizabeth; Marin, Maia Solange; Perez, Sandra (Elsevier, 2020)
Bovine herpesvirus (BoHV) types 1 and 5 are two closely related alpha-herpesviruses of cattle with neuroinvasive potential. BoHV-5 causes non-suppurative meningoencephalitis in calve whereas encephalitis caused by BoHV-1 has been occasionally reported. As an initial step to understand the biology of both BoHV types in neural cells, undifferentiated SH-SY5Y human neuroblastoma cells were infected with BoHV-1 strains Cooper and Los Angeles (LA), BoHV-5 strain 97/613 and A663, a BoHV-5/BoHV-1 natural recombinant. Cytopathic effect (CPE) in these cells was evident earlier for BoHV-5 strain 97/613 and CPE progression was slower for BoHV-1, particularly for Cooper strain. Virus antigen was detected as early as 8 h post-infection (hpi) for all strains, with the exception of BoHV-1 Cooper for which antigen expression was detectable by 24 hpi. All strains released detectable infectious virus in the extracellular medium by 8 hpi, confirming that undifferentiated SH-SY5Y cells are fully permissive to BoHV infection. Significantly different extracellular virus titers among the different strains were detected by 24 hpi, with BoHV-5 97/613 reaching the maximal virus production. The lowest extracellular titer was recorded for BoHV-1 Cooper at all the evaluated time-points. BoHV-1 Cooper, BoHV-1 LA and BoHV-5 97/613 had a steady increase in intracellular virus production. The evaluation of lysis plaques formation revealed that BoHV-5 A663 produced the largest plaques followed by BoHV-5 97/613. Both BoHV-1 strains produced smaller plaques when compared with BoHV-5. Despite a slower replicative cycle, strain A663 is more efficient in cell to cell dissemination. Thus, it is evident that BoHV-5 strains have growth advantages in undifferentiated neural cells compared with BoHV-1. This in vitro model might be useful to analyze the neuropathogenic potential of bovine alphaherpesviruses.